Empowerment of Health Cadres in the Early Detection of High-Risk Pregnancies: The Role of Motivation, Competence, and Social Support - Sumarmiati Sumarmiati; Muhammad Fanani; Yuli Peristiowati; Atik Setiawan Wahyuningsih (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Community health cadres serve as vital front-line actors in improving maternal health outcomes, particularly in the early identification of high-risk pregnancies. Operating as motivators, facilitators, and educators, their performance is influenced by internal attributes such as knowledge, skills, competence, and motivation, alongside external elements including social support. However, limited evidence exists on how these factors interact to influence their effectiveness. This study aimed to develop a structural model to analyze the relationships between these internal and external factors and their impact on cadre performance in early risk detection. Methods: A cross-sectional study with a correlational approach was conducted from January to May 2025. A total of 330 active health cadres from 37 community health centers in Kediri Regency, Indonesia, were selected using proportional random sampling. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore both direct and mediated effects among variables. Results: Knowledge (? = 0.044, p = 0.004), skills (? = 0.329, p < 0.001), and social support (? = 0.639, p < 0.001) significantly enhanced competence. Competence, in turn, strengthened motivation (? = 0.546, p < 0.001), which had the strongest direct effect on performance (? = 0.319, p = 0.043). Social support and skills indirectly improved performance through competence and motivation. The final model demonstrated good fit (SRMR = 0.046; NFI = 0.91; RMS_theta = 0.08) and explained 68% of the variance in cadre performance (R² = 0.68). Conclusion: Competence and motivation act as key mediators linking individual capacities and social support to performance. Strengthening these aspects through structured training and continuous social reinforcement is essential to enhance early detection of high-risk pregnancies and improve maternal health outcomes.